Enhancing laboratory biosafety management: a comprehensive strategy from theory to practice - Tang, Qin; Yan, Fei; Yuan, Lu; Tang, Ying; Chen, Hui; Sun, YuTing; Yang, Mi; Song, GuoLin (Frontiers in Public Health, 2024)
Objective: This study examines biosafety management practices in a psychiatric hospital's laboratory in China, focusing on how outdated information technology impacts the hospital's ability to respond to public health emergencies. The goal is to enhance the hospital's emergency response capabilities by updating risk assessments, biosafety manuals, and implementing a comprehensive quality management system alongside a specialized infection control system for significant respiratory diseases. Methods: We utilized an integrated research approach, expanding the scope of risk assessments, updating the biosafety manual according to the latest international standards, and implementing a quality management system. A specialized infection control system for significant respiratory diseases was introduced to improve emergency response capabilities.Results: Updated risk assessments and a new biosafety manual have significantly improved the identification and management of biosafety threats. Implementing new quality management and infection control systems has enhanced response efficiency and operational standardization.Conclusion: The measures taken have strengthened the biosafety management and emergency response capabilities of the laboratory department, highlighting the importance of information technology in biosafety management and recommending similar strategies for other institutions.